2022
DOI: 10.3389/fpubh.2022.994137
|View full text |Cite
|
Sign up to set email alerts
|

A core framework of “mountain management–water management–moist city” for sponge city special planning: The case of northwestern China

Abstract: Sponge city special planning represents a basis for sponge city construction in China. It has a leading role in problem-oriented, effect-centered comprehensive, and coordinated construction. In accordance with the Interim Provisions on the Formulation of Sponge City Special Planning, China has gradually established a standardized method for formulating sponge city special planning based on the “four-water” framework. While this method emphasizes the normalization of planning contents, it has limitations when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They also assessed the damages resulting from urban floods across various rainfall return periods (Wang et al, 2021). Wu suggested that the development of LID systems should not alone emphasize construction standardization, but also incorporate diverse governance concepts that align with specific regional features (Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They also assessed the damages resulting from urban floods across various rainfall return periods (Wang et al, 2021). Wu suggested that the development of LID systems should not alone emphasize construction standardization, but also incorporate diverse governance concepts that align with specific regional features (Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%